Nesfatin-1 and irisin levels in response to the soccer matches performed in morning, afternoon and at night in young trained male subjects - Ozcelik, Oguz; Algul, Sermin; Yilmaz, Bayram (C M B Assoc, 2018)
This study aimed to investigate the potential effects of acute soccer matches performed in morning, afternoon and at night on both nesfatin-1 and irisin levels in trained subjects. Total of 20 male subjects performed in soccer matches at three different times of day: morning, afternoon, and night. Pre- and post-match venous blood samples were taken, and levels of both nesfatin-1 and irisin were analysed using the enzyme-linked immunosorbent assay (ELISA). Following all matches, the subjects' irisin levels increased significantly in all subjects (p < 0.0001). Nesfatin-1 levels were also increased after the matches; however, the increase was statistically significant for morning (P=0.01) and night-time (p=0.009). The subjects' nesfatin-1 levels did not increase in all subjects and decrease of nesfatin-1 levels observed in some subjects after matches. This study finds that soccer matches performed different workout times have strong stimulatory effects on irisin levels in all subjects but nesfatin-1 response varied among the subjects and it did not change significantly in afternoon match.
Keywords: Energy; Irisin; Metabolism; Nesfatin-1; Soccer match